Transitional Experience of International Students from African Countries Studying in Canada: A Systematic Literature Review - Toyosi Bamgboye (Canadian Journal for New Scholars in Education)
The purpose of this paper is to understand the transitional experience of international students from African countries who are studying in Canada, provide guidance on how post-secondary institutions in Canada can best support these international students from African countries to enable them to settle and succeed in their academics, add to the limited body of literature on African students in Canada ​and give a voice and advocate for African students in BC. Therefore, this research aims to answer the following questions in line with this purpose: